A formação inicial para o trabalho de pedagogas com as artes visuais na Educação Infantil - Cipriano, Gabriela da Silva (Universidade Federal de São Carlos, 2021)
The object of this research is the initial preparation and the pedagogue's practice with the Visual Arts in Early Childhood Education. We tried to answer the question-problem “how Art education has been done in the Pedagogy course and how have the teaching practices been built in preschool regarding educational practice with Visual Arts?” Through a bibliographical research, interspersed with personal reports of my preparation and internship experiences, the work is structured as follows: in Chapter I, called “Travelled paths”, a narrative is made about the research paths and the methodological procedures. In Chapter II, which offers the entire theoretical framework of the investigation, three questions arising from the main problem question are answered: what is the panorama of the Art discipline in Pedagogy courses; what are the main relationships of Early Childhood Education with artistic languages; and what are the conditions, times, spaces, physical structure and materials that teachers have to work with the Visual Arts with children? Then there are the Final Considerations and the Bibliographic References. As a result, it was found that artistic education in the Pedagogy course is crucial and essential for: the construction of a teaching identity that approaches emancipation and critical capacity; the fight, in the field of teacher education, against conservatism and technicality; expand, in teachers education, the right of access to cultural and artistic collections built by humanity, including Afro-Brazilian, African and indigenous cultures; prepare pedagogues to work with artistic languages in Early Childhood Education, so that they feel able to plan and carry out pedagogical actions involving the arts, respecting the knowledge of different cultures, the creative dimension, the necessary integral education of children, as well as their rights to participation, exploration and construction of learning through play.
Initial preparation for the work of pedagogues with the visual arts in Early Childhood Education
Keywords: Artes; Art; Pedagogia; Pedagogy; Educação infantil; Early childhood education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO